Performance of High Strength POFA Concrete in Acidic Environment - Ahmed, Mokhtar Albshir Budiea; Mohd Warid, Hussin; Khairunisa, Muthusamy; Mohamed, Ismail El Gelany (ISSR, 2010)
Malaysia as the world’s largest exporter of palm oil has been facing problem in disposing palm oil fuel ash, a by-product of palm oil mill since many years ago. The discovery made by researchers of Universiti Teknologi Malaysia last century in revealing the potential of this finely ground waste as a partial cement replacement in normal concrete has stem efforts towards studying the possibility of using it in high strength concrete production. This paper illustrates the durability aspect of high strength concrete produced using POFA of different fineness when exposed to acidic environment. Two POFA concrete mixes with different fineness termed (POFA 45 and POFA 10) at 20% replacement level by weight of cement and an OPC concrete mix functioning as control specimen termed Po was considered in this study. All the specimens were subjected to water curing for 28 days before immersed in the hydrochloric solution having pH 2 for 1800 hours. The progressive deterioration was evaluated through mass changing of the specimens, visual inspection and relative compressive strength determinations. Conclusively, the study found that increase in the POFA fineness enhances the resistance of high strength POFA concrete towards acid attack.